Pengembangan sikap toleransi beragama siswa melalui kegiatan keagamaan di SMPK Widyatama Batu - Cicilia Dyah Intan Puspitasari; A. Rosyid Al Atok; Petir Pudjantoro (Jurnal Integrasi dan Harmoni Inovatif Ilmu-Ilmu Sosial (JIHI3S), 2022)
This study aims to find out the existing religious activities, find out religious activities specifically aimed at developing students' religious tolerance attitudes, know the practice of developing religious tolerance attitudes through student activities carried out, know the obstacles faced in the development process attitudes of religious tolerance through student activities, and knowing solutions to face obstacles in the process of developing religious tolerance through student activities at SMPK Widyatama Batu. The method in this study uses a qualitative approach with a descriptive type of research. Data collection techniques use interviews, observations, and documentation. The data analysis technique uses Miles and Huberman's interactive analysis. The results of this study are (1) religious activities, namely faith building, religious holidays celebrations, interfaith prayers, and Christmas Action and APP, (2) religious activities devoted to developing students' religious tolerance attitudes are celebrations of religious holidays, interfaith prayers, and National Scripture Month, (3) development practices Students' tolerance attitudes at Christmas activities together are carried out by introducing students to a religious activity, examples from teachers, and active involvement of students, (4) the obstacles faced are the COVID-19 pandemic, and the decline in student enthusiasm during the activity, (5) the solution is the use of technology, the form of activity is changed to a competition, conducting interlude activities that attract students' attention again. Penelitian ini bertujuan untuk mengetahui kegiatan keagamaan yang ada, mengetahui kegiatan keagamaan yang ditujukan khusus untuk mengembangkan sikap toleransi beragama siswa, mengetahui praktik pengembangan sikap toleransi beragama melalui kegiatan siswa yang dilakukan, mengetahui hambatan yang dihadapi dalam proses pengembangan sikap toleransi beragama melalui kegiatan siswa, dan mengetahui solusi menghadapi hambatan dalam proses pengembangan toleransi beragama melalui kegiatan siswa di SMPK Widyatama Batu. Metode dalam penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian deskriptif. Teknik pengumpulan data menggunakan wawancara, observasi, dan dokumentasi. Teknik analisis data menggunakan analisis interaktif Miles dan Huberman. Hasil penelitian ini adalah (1) kegiatan keagamaannya yaitu bina iman, perayaan hari besar keagamaan, doa lintas agama, dan Aksi Natal serta APP, (2) kegiatan keagamaan yang dikhususkan untuk mengembangkan sikap toleransi beragama siswa adalah perayaan hari besar keagamaan, doa lintas agama, dan Bulan Kitab Suci Nasional, (3) praktik pengembangan sikap toleransi siswa pada kegiatan Natal bersama dilakukan dengan mengenalkan siswa dengan suatu kegiatan keagamaan, contoh dari guru, dan pelibatan aktif siswa, (4) hambatan yang dihadapi adalah pandemi COVID-19, dan menurunnya antusias siswa saat kegiatan berlangsung, (5) solusinya adalah pemanfaatan teknologi, bentuk kegiatan diubah menjadi lomba, melakukan kegiatan selingan yang menarik perhatian siswa kembali.